ANALYSIS OF SAUDI DEMAND FOR IMPORTED BROILER CHICKENS - M. M. Alderiny; S. B. Ahmed (Journal of Animal and Plant Sciences, 2019)
The study was aimed to analyze the Saudi demand for imported broiler chickens from Brazil, France, and other countries. The ideal demand model for time series data on imported quantities and values were adjusted during the period 1990-2016. Since the model equations are nonlinear in transactions, Non-linear least squares in estimating the parameters of the model. The results showed that the model has achieved the condition of addition, and the equations are termed as homogeneous from the zero degrees, and it was found that all the price elasticity’s (own and cross both) and the elasticity of the expenditure agree with the economic theory. But it was noted that the demand for broiler chickens from France was highly elastic to the change in the price of Brazil and other countries. It was also noted that demand was found less elastic for total expenditure change for broiler chickens imported from other countries and that it was equally elasticity to change in the prices of Brazil and France chickens. The prediction of imported broiler chickens showed that there was a general trend expected to increase imports from Brazil and France.
Keywords: Broilers chicken; imports; price elasticity; cross and expenditure elasticity; Almost ideal demand system; Saudi Arabia